Impact of abiotic and biogeochemical processes on halogen concentrations (Cl, Br, F, I) in mineral soil along a climatic gradient. Issue 9 (9th March 2022) - Neidhardt, Harald; Lemke, Erik; Epp, Tatjana; Marks, Michael A. W.; Markl, Gregor; Oelmann, Yvonne
Abstract : Halogens in soil are closely linked to abiotic processes, biota and pedogenesis, and thus to the availability of water; vertical halogen depth patterns become less pronounced with increasing dryness. Abstract : In contrast to earlier ideas that halogens behave inertly in soil, extensive biogeochemical cycling of fluorine (F), chlorine (Cl), bromine (Br) and iodine (I) has been shown for temperate forests. To further advance our understanding of halogen behaviour in soil beyond humid temperate forests, we sampled soil profiles in protected areas along the Chilean Coastal Cordillera, representing a pronounced climatic gradient spanning from arid to humid. Halogen concentrations in soil were analysed by combustion ion chromatography. Highest average total halogen concentrations occurred at the arid site (Cl, F: 4270 and 897 mg kg −1 ) as well as the humid end of the climatic gradient (Br, I: 42.6 and 9.8 mg kg −1 ). Vertical distribution patterns of halogens were most pronounced at the humid end of the gradient and became less distinct under drier climate. The climatic gradient demonstrates the important role of biotic processes ( e.g. the halogenation of organic matter) on the retention of halogens in the soil. However, this climate-specific role may be overridden by mainly abiotic processes within a given climate zone ( e.g. weathering, leaching, sorption to secondary soil minerals, evaporative enrichment), resulting in vertical relocation of halogens in the soil. Since some of these processes oppose each other, complex interactions and depth distributions of F, Cl, Br and I occur in the soil. In summary, our findings provide new insights into the fate of halogens in mineral soil of different climatic zones, which is important, for example, when radiohalogens are deposited on a large scale after nuclear accidents.